2013
DOI: 10.1016/j.msec.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen content in titanium and a titanium–zirconium alloy after acid etching

Abstract: Dental implant alloys made from titanium and zirconium are known for their high mechanical strength, fracture toughness and corrosion resistance in comparison with commercially pure titanium. The aim of the study was to investigate possible differences in the surface chemistry and/or surface topography of titanium and titanium-zirconium surfaces after sand blasting and acid etching. The two surfaces were compared by X-ray photoelectron spectroscopy, secondary ion mass spectroscopy, scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 142 publications
(143 reference statements)
3
30
0
Order By: Relevance
“…On the modSLA surface of TiZr, additional amounts of aluminum and zirconium were detected, and besides TiO 2 molecules, also ZrO 2 molecules were found (Table 9.4 ) [ 107 ]. The presence of Al can be explained by Al 2 O 3 residuals due to the sandblasting process [ 103 ].…”
Section: Physical and Chemical Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…On the modSLA surface of TiZr, additional amounts of aluminum and zirconium were detected, and besides TiO 2 molecules, also ZrO 2 molecules were found (Table 9.4 ) [ 107 ]. The presence of Al can be explained by Al 2 O 3 residuals due to the sandblasting process [ 103 ].…”
Section: Physical and Chemical Propertiesmentioning
confidence: 97%
“…titanium, it has been found that titanium-zirconium alloys show superior biomechanical properties, identifi ed by increased hardness and tensile strength [ 108 ]. Since titanium, zirconium, as well as the TiZr alloy show the α-phase crystal structure at room temperature and pressure [ 106 ], the manufacturing procedure (sandblasting and acid-etching, rinsing under N 2 protection, storage in isotonic NaCl solution) for creating the modSLA surface on c.p titanium can be transferred to this particular TiZr alloy [ 107 ]. Thus, Results presented as mean ± SD, n = 5 for each surface 9 Sandblasted and Acid-Etched Implant Surfaces With or Without High Surface Free Energy one specifi c advantage of this TiZr alloy is its increased biomechanical strength compared to c.p.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the spectra of the Ti substrate (a-phase titanium, JCPDS #44-1294), the peaks of titanium hydride (JCPDS #09-0371) can be seen in Fig. 4a and c, mainly due to hydrogen incorporation into the Ti substrate during the process of acid etching [45]. On the contrary, no crystalline peaks of TiO 2 were identified from the asprepared micro/nano-textured Ti surface (Fig.…”
Section: Surface Chemical Composition and Phase Analysismentioning
confidence: 99%
“…As the metal is left without its dense protective oxide layer, the small ions of hydrogen diffuse rapidly into the metal. The sub-surface is therefore enriched with hydrogen 25 , and when saturation in hydrogen is reached, titanium hydride is formed.…”
mentioning
confidence: 99%